Physical Properties of Buckwheat Water Biscuits Formulated from Fermented Flours by Selected Lactic Acid Bacteria - Wronkowska Małgorzata; Jeliński Tomasz; Majkowska Anna; Zieliński Henryk (Polish Journal of Food and Nutrition Sciences, 2018)
The growth of lactic acid bacteria during liquid-state fermentation of buckwheat flour and changes in pH during the process were analyzed. Eight strains of Lactobacillus were selected as the most active strains used to obtain new fermented flours. Physical properties of buckwheat water biscuits formulated from these fermented flours were studied.